2009
DOI: 10.1103/physrevb.80.184515
|View full text |Cite
|
Sign up to set email alerts
|

Competing phases, strong electron-phonon interaction, and superconductivity in elemental calcium under high pressure

Abstract: The observed "simple cubic" (sc) phase of elemental Ca at room temperature in the 32-109 GPa range is, from linear response calculations, dynamically unstable. By comparing first principle calculations of the enthalpy for five sc-related (non-close-packed) structures, we find that all five structures compete energetically at room temperature in the 40-90 GPa range, and three do so in the 100-130 GPa range. Some competing structures below 90 GPa are dynamically stable, i.e., no imaginary frequency, suggesting t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 39 publications
(55 reference statements)
3
30
1
Order By: Relevance
“…The diffraction patterns for these structures are even distinctly more different from that of the sc structure. This observation does not therefore provide support for a previous suggestion 17 that, at room temperature, the observed sc phase is an average structure of several competing structures although it is possible that energetically very close structures not yet considered could be contributing.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The diffraction patterns for these structures are even distinctly more different from that of the sc structure. This observation does not therefore provide support for a previous suggestion 17 that, at room temperature, the observed sc phase is an average structure of several competing structures although it is possible that energetically very close structures not yet considered could be contributing.…”
Section: Resultscontrasting
confidence: 54%
“…Moreover, Yao et al 15 and Oganov et al 16 also predicted the existence of a lower enthalpy I4 1 / amd phase at low temperature. Very recently, Yin et al 17 provided another interpretation along this line. They assumed that since the proposed models are energetically and structurally very close to sc, the observed "sc" phase could be interpreted as a highly anharmonic phase derived from a spatially inhomogeneous and dynamically fluctuating combination of multiple structures.…”
Section: Introductionmentioning
confidence: 94%
“…The excellent agreement between our experimental and theoretical results allowed us to not only reconcile previous unexplained anomalies, but also to shed light onto the complex behavior of metastable phases under pressure. Elemental phosphorus, like other elements [53] and compounds [54], has the tendency to form many polymorphs that differ substantially in their electronic and superconducting properties and can coexist in metastable forms over different pressures. In this work, we showed that many of these exhibit critical temperatures which are distinctively higher than the putative ground-state structures.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies, which require the use of more accurate methods and measurements are necessary. Fluctuations and distortions at finite-temperature among several quasidegenerate structures, as proposed in [8], also need to be considered. …”
Section: Comment On ''Structural Prediction and Phase Transformation mentioning
confidence: 99%